Effect of Centella Asiatica (L.) Extract on Serum Levels of IL-6 and IL-10 in Traumatic Brain Injury Rat - Nurafia, Sindy; Prihatno, MM Rudi; Novrial, Dody; Nafiisah, Nafiisah (Jurnal Neuroanestesi Indonesia, 2025)
Introduction: Traumatic brain injury (TBI) represents a major global health burden, because it is the foremost causes of death, particularly in young adults. Elevated IL-6 and IL-10 serum levels in severe TBI have been identified as an early indicator of unfavorable clinical outcomes. Pegagan (Centella asiatica (L.)) has antioxidant, neuroprotective, neurogenerative, anti-inflammatory properties. Our goal of this study was to find out what happened to IL-6 and IL-10 levels in blood of the TBI rat model when they were given pegagan extract (Centella asiatica (L.)). Subject and Method: experimental research design. For 3 days, there were 4 groups of male Wistar strain rats (Rattus norvegicus) subjects, consisting of three treatment groups (pegagan extract doses of 300 mg/kgBW, 500 mg/kgBW, and 1000 mg/kgBW) and one control group. On the 4th day, blood was taken, and we continued to examine IL-6 and IL-10 serum levels by ELISA. Result: A dose-dependent and significant increase of IL-6 and IL-10 serum levels was observed in the treatment groups compared with control group. Conclusion: In TBI rat model, administration of pegagan (Centella asiatica (L.)) extract increases IL-6 and IL-10 levels.